1999
DOI: 10.1021/bi990381x
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Bovine Protein Tyrosine Phosphatase Dimer Reveals a Potential Self-Regulation Mechanism,

Abstract: The bovine protein tyrosine phosphatase (BPTP) is a member of the class of low-molecular weight protein tyrosine phosphatases (PTPases) found to be ubiquitous in mammalian cells. The catalytic site of BPTP contains a CX 5 R(S/T) phosphate-binding motif or P-loop (residues 12-19) which is the signature sequence for all PTPases. Ser19, the final residue of the P-loop motif, interacts with the catalytic Cys12 and participates in stabilizing the conformation of the active site through interactions with Asn15, also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 29 publications
3
58
0
1
Order By: Relevance
“…Previous crystal structural analyses revealed that several conserved residues, including Asn-15, Ser-19, Ser-43, and His-72, are involved in the stabilization of the P-loop of BPTP. 8,11 This is supported by the present dynamics simulations. His-72 participates in hydrogen …”
Section: Figuresupporting
confidence: 85%
See 1 more Smart Citation
“…Previous crystal structural analyses revealed that several conserved residues, including Asn-15, Ser-19, Ser-43, and His-72, are involved in the stabilization of the P-loop of BPTP. 8,11 This is supported by the present dynamics simulations. His-72 participates in hydrogen …”
Section: Figuresupporting
confidence: 85%
“…Overall, the structure of the unligated enzymes (both the wildtype and C12S mutant) showed minimal variations in comparison with the X-ray structure, which contains a phosphate ion as substrate. 8,11,12,46 The rms deviations between the two structures are 1.0 Å for all heavy atoms and 0.7 Å for the backbone heavy atoms in the wild-type enzyme. The backbone heavy atoms in the P-loop (residues 12-19) region only have an average deviation of 0.3 Å in comparison with the ligated X-ray structure.…”
Section: The Wild-type Enzyme and C12s Mutantmentioning
confidence: 94%
“…Because the compound binds to the enzymesubstrate complex, it may assist in trapping endogenous substrate in the active site of the enzyme in inhibitor-treated cells. Furthermore, if PTPMT1 does indeed exist as a dimer, the compound may also prove useful in efforts to study the enzyme's structure using X-ray crystallography by stabilizing the dimer (Tabernero et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of bovine PTPase (bPTPase) (PDB ID: 1DG9) has been resolved at 1.90 Å [51], which shows about 41% sequence identities and shares a common signature motif C(X) 5 R(S/T) with PTPase. The structure of 1DG9 reveals a dimer formed by Tyr131 and Tyr132 from two different monomers at pH 7.0 in 0.1 M Tris.…”
Section: Discussionmentioning
confidence: 99%